Plants; Stress & Proteins - Qingsong Lin (Frontiers Research Topics, 2017)
Biotic and abiotic stress factors deliver a huge impact on plant life. Biotic stress factors such as damage through pathogens or herbivore attack, as well as abiotic stress factors like variation in temperature, rainfall and salinity, have placed the plant kingdom under constant challenges for survival. As a consequence, global agricultural and horticultural productivity has been disturbed to a large extent. Being sessile in nature, plants cannot escape from the stress, and instead adapt changes within their system to overcome the adverse conditions. These changes include physiological, developmental and biochemical alterations within the plant body which influences the genome, proteome and metabolome profiles of the plant. Since proteins are the ultimate players of cellular behavior, proteome level alterations during and recovery period of stress provide direct implications of plant responses towards stress factors. With current advancement of modern high-throughput technologies, much research has been carried out in this field. This e-book highlights the research and review articles that cover proteome level changes during the course or recovery period of various stress factors in plant life. Overall, the chapters in this e-book has provided a wealth of information on how plants deal with stress from a proteomics perspective.